The role of ovipositor extrusion during courtship in female Drosophila melanogaster - Brotas, Margarida Caldeira (2019)
Tese de mestrado, Biologia Evolutiva e do Desenvolvimento, Universidade de Lisboa, Faculdade de Ciências, 2018